2020
DOI: 10.1111/cen.14345
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and hormonal side effects of mitotane treatment for adrenocortical carcinoma: A retrospective study in 50 Danish patients

Abstract: ObjectiveMitotane is used in the treatment of adrenocortical carcinoma (ACC). Metabolic and hormonal side effects of mitotane, the effect of subsequent treatment with statins and hormones and the effects of discontinuation of mitotane were assessed.Patients and methodsFifty patients were included. Lipid profiles, thyroid hormones, sex hormones and adrenal function from first year of mitotane treatment and after cessation were evaluated.ResultsAfter 6 months of mitotane treatment total cholesterol increased fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 25 publications
1
36
1
Order By: Relevance
“…Only three studies specified the need for increased steroid coverage due to serum ACTH level elevation, or to signs and symptoms of adrenal insufficiency, as an endocrine adverse event (13/53 patients, 24.5%) [ 19 , 22 , 40 ]. Mineralocorticoid replacement was administered in a total of 67 of 182 patients in six studies [ 21 , 29 , 31 , 34 , 40 , 43 ]. Moreover, another study reported the need for fludrocortisone replacement therapy, but the proportion of patients was unclear [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Only three studies specified the need for increased steroid coverage due to serum ACTH level elevation, or to signs and symptoms of adrenal insufficiency, as an endocrine adverse event (13/53 patients, 24.5%) [ 19 , 22 , 40 ]. Mineralocorticoid replacement was administered in a total of 67 of 182 patients in six studies [ 21 , 29 , 31 , 34 , 40 , 43 ]. Moreover, another study reported the need for fludrocortisone replacement therapy, but the proportion of patients was unclear [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, the authors failed in the identification of any predictors of the HPA axis recovery [ 34 ]. Accordingly, another study reported that 15 out of 24 patients tested with ACTH stimulation test showed a recovery of adrenal function 6 months after the mitotane therapy discontinuation [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In experimental models, the use of mitotane has been associated to an impaired TSH expression and TRH responsivity [68]. In clinical studies, a marked reduction in FT4 levels (inversely correlated with mitotane concentrations) has been reported, but interestingly, TSH did not change accordingly [69]. The explanation can be attributed to a possible "central hypothyroidism" or alternatively to an impairment of deiodinase activity with a change in FT4/FT3 ratio.…”
Section: Effects Of Steroidogenesis Inhibitors On Hpt Axis Activitymentioning
confidence: 99%